(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The increasing HIV-AIDS with some cases in 2014 make be concerned by local governement, NGOs and people in Malang. The volunteers are the backbone in the process of preventing the wider of HIV-AIDS. The method that is used by volunteers are the Behavior Change Communication (BCC) program as a method to persuade people who are injected HIV-AIDS and people who has high risk in HIV-AIDS. Furthermore, the BCC is also a method to promote the importantce of having save sex in order to avoid being injected by HIV-AIDS. Allave purpose to decrease and prevent HIV-AIDS di Malang. The volunters are the actors in BCC program so they need high skill to employ BCC as tool for persuasive people with HIV-AIDS (ODHA) or high risk of HIV-AIDS (RESTI) to have save sex. Hence, the research have purpose to identify and evaluate how strategy the volunter and institution in improving capacity building through workhop, periodictly meeting, improving mass media and application BCC based on situation and social setting from ODHA and RESTI as significance group. This research use mixed method: quantitative and qualitative methods. This research show that capacity building toward volunteer is complited during recruitment and conducting program. Capacity building is conducted by some institutions: NGOs, fundings and government. Besides, BCC is effective for preventing HIV-AIDS which save sex is conducted by RESTI as adopters group.